PEMBAGIAN HARTA BERSAMA MENURUT UNDANG-UNDANG PERKAWINAN DALAM KASUS PUTUSAN NOMOR 161/PDT.G/2019/PN.BDG - Lydia Amelia; Aline Gratika Nugrahani (Reformasi Hukum Trisakti, 2022)
After marriage, unification of assets is created and called total assets. It’s undeniable many couples' quarrels leads to a divorce. In first degree divorce process, judge is obliged to carry out mediation process, and mediator accompanies the process as neutral party. If both parties agree to mediate, then the agreement is in form of settlement. However, what if the deed of reconciliation is submitted to a notary before filing for divorce, and some assets are not listed in the deed of reconciliation after final lawsuit is filed. The research’s problem: How is the distribution of joint assets according to Law Number 1 of 1974 and How does the effect of the Deed of Settlement on the distribution of joint assets in the case number 161/Pdt.G/2019 /PN. Bdg?. The research is a descriptive legal research, using secondary data, supported by primary data and The conclusions are drawn using deductive method. This research states that Article 37 of Law Number 1 of 1974 concerning Marriage that if a marriage is dissolved due to divorce, the assets settled in accordance with applicable laws and settlement agreement is made. There are no more disputes regarding the distribution of joint assets agreed in settlement document.